2010
DOI: 10.1016/j.joen.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Final Rinse Optimization: Influence of Different Agitation Protocols

Abstract: Introduction: This study examined the effect of different root canal irrigant agitation protocols in the penetration of an endodontic irrigant into dentinal tubules. Methods: Fifty-six human single-rooted teeth were shaped with nickel-titanium instruments, and a final rinse of 5% sodium hypochlorite labeled with 0.2% alizarin red was performed. Specimens were assigned to 7 groups (N = 8) and submitted to the following rinse activation protocols: no agitation (control group), K-File or gutta-percha agitation, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
1
13

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 35 publications
8
73
1
13
Order By: Relevance
“…These findings agree with those of Paragliola et al (20), who also reported better effectiveness for ultrasonic activation than for a plastic file in improving penetration of solutions into dentinal tubules. PUI also has advantages over conventional irrigation in root canal debridement (20) and in creating cavitation and acoustic streaming (25). As compared with the PUI group, QMix in combination with EC probably resulted in lower increases in movement and flow, which explains the higher SL scores.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings agree with those of Paragliola et al (20), who also reported better effectiveness for ultrasonic activation than for a plastic file in improving penetration of solutions into dentinal tubules. PUI also has advantages over conventional irrigation in root canal debridement (20) and in creating cavitation and acoustic streaming (25). As compared with the PUI group, QMix in combination with EC probably resulted in lower increases in movement and flow, which explains the higher SL scores.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, irrigation methods and devices are used in association with disinfection agents, both to enable better cleaning (19) and reduce the time required for an effect (20). Previously reported methods include negative pressure irrigation (21), sonic activation (20,22), passive ultrasonic irrigation (19), manual dynamic activation with a K-file (20) or gutta-percha cones (20,21), continuous ultrasonic irrigation (21), use of a self-adjusting file with simultaneous irrigation and scrubbing (19), and plastic endodontic finishing files (20,23), among other methods.…”
Section: Originalmentioning
confidence: 99%
“…24 Energy is transmitted from a file or smooth oscillating wire to the irrigation by ultrasonic waves, producing a stream and cavitation of the irrigating solution disrupting the vapor lock. Paragliola et al 25 and Lui et al 26 concluded…”
mentioning
confidence: 99%
“…5) In comparison, although sonic vibration does not cut the root canal, it has been pointed out that it is less effective than ultrasonic vibration. [24][25][26][27] We therefore and that its effect decreased over time. 28) Continuous irrigation is required to improve the efficacy of an irrigant, and this would prevent a decline in the efficacy of the irrigant.…”
Section: Introductionmentioning
confidence: 75%